Synthesis and Performance of LiFePO4-C/Graphene Composite - NAN Wen-zheng; YAN Shao-jiu; PENG Si-kan; ZHANG Xiao-yan; LIU Da-bo; DAI Sheng-long (Cailiao gongcheng, 2018)
LiFePO4-C/graphene composite was successfully prepared by a facile approach of grinding, ultrasonic dispersion, stirring and drying and used as the cathode material for lithium-ion batteries.The structure and morpholgy of as-prepared LiFePO4-C/graphene composite material was characterized with transmission electron microscopy,scanning electron microscopy, X-ray diffraction and Raman spectroscopy,and the electrochemical performance was tested using coin cells assembled in an argon-filled glovebox. SEM images show that in the as-prepared material, graphene nanoflakes are adhered on the surface of LiFePO4-C particles, and uniformly dispersed in the composite material forming an effective 3D conducting network. Electrochemical tests show that after adding 2% of graphene, rate and cycling performances of the LiFePO4-C/graphene composite material are obviously improved. For the rate performance, a high reversible capacity of 94.2mAh·g-1 is achieved at 5C rate,which is more than 2.53 times higher than that of pristine LiFePO4-C; For cycling performance, the composite material shows a low capacity decay rate of 9.6% when cycles under 1C rate for 100 times,which is lower than pure LiFePO4-C (43.5%). The electrochemical performance enhancement can be mainly ascribed to the effective 3D conducting network formed by graphene nanoflakes with superior conductivity.